Multidimensional Analysis of Conversational Telephone Speech - Köster, Friedemann; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents a new diagnostic information methodology to assess the quality of conversational telephone speech. For this, a conversation is separated into three individual conversational phases (listening, speaking, and interaction), and for each phase corresponding perceptual dimensions are identified. A new analytic test method allows gathering dimension ratings from non-expert test subjects in a direct way. The identification of the perceptual dimensions and the new test method are validated in two sophisticated conversational experiments. The dimension scores gathered with the new test method are used to determine the quality of each conversational phase, and the qualities of the three phases, in turn, are combined for overall conversational quality modeling. The conducted fundamental research forms the basis for the development of a preliminary new instrumental diagnostic conversational quality model. This multidimensional analysis of conversational telephone speech is a major landmark towards deeply analyzing conversational speech quality for diagnosis and optimization of telecommunication systems. .
Introduction -- Fundamentals -- Speech Quality in a Telephone Conversation -- Perceptual Quality Space in a Telephone Conversation -- Direct Scaling of Perceptual Dimensions in a Conversational Situation -- Conversational Validation Experiments -- Resulting Quality Profile in a Telephone Conversation -- Instrumental Diagnostic Conversational Quality Modeling -- Conclusions.
Keywords: Signal processing; Application software; Customer services; Signal, Speech and Image Processing; Computer and Information Systems Applications; Customer Service and Call Center